IMPLEMENTING EIT-4-BPSD AND MEASURING THE USE OF PERSON CENTERED APPROACHES TO BPSD IN NURSING HOME RESIDENTS. (11th November 2018) - Resnick, B; Mogle, J
Abstract: Behavioral and Psychological Symptoms of Dementia (BPSD) include aggression, agitation, resistiveness to care, depression, anxiety, apathy and hallucinations and are exhibited by up to 90% of nursing home residents living with dementia. BPSD result in negative health outcomes decline in physical functioning and high cost of care. Despite regulatory requirements, less than 2% of nursing homes consistently implement person-centered behavioral approaches. We developed a real world practical solution to assuring that staff provide behavioral interventions for BPSD while optimizing function, preventing adverse events and improving quality of life of residents. The implementation process is based on use of the Evidence Integration Triangle (EIT), a parsimonious, community-engaged participatory framework that is well-suited to the complexity and variability found in the nursing home environment. EIT is a readily applied framework that brings together evidence informed person-centered approaches for management of BPSD and facility stakeholders. To optimally address behavior change among staff in nursing home settings additional theoretical support for the intervention, EIT-4-BPSD, includes the Social Ecological Model and Social Cognitive Theory. To test the implementation process measurement of outcomes needs to be practical, effective, and address the facility, staff and residents. This symposium will describe EIT-4-BPSD and several of the measures used to address the implementation process and establish the effectiveness of the EIT-4-BPSD approach. Specifically we describe the psychometric testing of a quality of life measure, a measure of the care plans developed in the settings and a measure of the environment and policies within these settings.